The Effect Of Variety Training On Dribbling Skills Of Futsal Extracurricular Students At SMP Negeri 44 Seluma - Lestari, Nice Anindia; Perdima, Feby Elra; Asnawati, Asnawati (Universitas Dehasen Bengkulu, 2025)
This study aims to determine the effect of Variation training on futsal extracurricular dribbling skills at SMPN 44 Seluma. This research is motivated by the low mastery of the ball in futsal games, which is caused by the level of dribbling that is still inadequate. This research is a Quantitative Research experiment using pretest and posttest one group design techniques. The population in this study were futsal extracurricular students at SMP N 44 Seluma and a sample of 20 people. The data collection technique in this study used total sampling technique. The results of this study indicate that the pretest average reached 18.05 and the posttest average was 16.69. This shows a positive increase of 1.36% after the application of variation training exercises on dribbling skills, which shows that the exercise has a better impact than before the training is done.